An In-Vitro Assay Estimating Changes in Melanin Content of Melanoma Cells due to Ultra-Dilute, Potentized Preparations - Munshi, Renuka; Joshi, Samidha; Talele, Gitanjali; Shah, Rajesh (Homeopathy, 2019)
Introduction The authors had previously conducted an in-vitro study to observe the effect of homeopathic medicines on melanogenesis, demonstrating anti-vitiligo potential by increasing the melanin content in murine B16F10 melanoma cells. A similar experiment was performed using further homeopathic preparations sourced from kojic acid (KA), hydrogen peroxide (H2O2; HP), 6-biopterin (BP), and [Nle4, D-Phe7]-α-melanocyte-stimulating hormone (NLE), some of which are known to induce vitiligo or melano-destruction at physiological dose.Materials and Methods The homeopathic preparations of BP, KA, NLE, and HP were used in 30c potency. Alcohol and potentized alcohol were used as vehicle controls. Prior to starting the main experiment, the viability of B16F10 melanoma cells after treatment with study preparations was assayed. Melanin content (at 48 h and 96 h) and tyrosinase activity in melanocytes were determined.Results At the end of 48 hours, NLE and HP in 30c potency had a significantly greater melanin content (p = 0.015 and p = 0.039, respectively) compared with controls; BP and KA in 30c potency had no significant effects. No significant changes were seen at the end of 96 hours. KA, NLE, HP, and vehicle controls showed an inhibition of tyrosinase activity.Conclusion The study demonstrated melanogenic effects of two homeopathic preparations. Further research to evaluate the therapeutic efficacy of these medicines is warranted.
Keywords: melanin; melanoma cells; vitiligo; ultra-dilution; potentization; homeopathy